Diagnostics of anemia and iron deficiency in patients with chronic heart failure - O.O. Khanyukov; L.A. Pesotskaya; L.V. Sapozhnychenko; O.O. Pampukha (Medičnì Perspektivi, 2023)
According to the recommendations of the European Society of Cardiology (ESC) 2021 for the management of patients with chronic heart failure (CHF), it is necessary to take into account the iron level in the diagnosis of all patients with firstly diagnosed heart failure (HF). Also the practical recommendations indicate that the assessment of iron deficiency is also carried out in patients with already confirmed CHF, especially if the symptoms of HF persist against the background of optimal treatment of the underlying disease, which necessitates knowledge of the diagnosis of anemia and iron deficiency in patients with CHF. The aim was review literature illustrating current data about diagnostics of iron deficiency and anemia in patients with CHF. In the work 28 sources from the Web of Science database and 7 sources from the PubMed database were analyzed. Anemia is diagnosed by hemoglobin levels. As criteria for iron deficiency, two parameters are used in clinical practice – ferritin level and transferrin saturation. The mean corpuscular volume of erythrocytes and the mean hemoglobin content in them were not reliable markers of iron deficiency and are not recommended for assessing iron deficiency in patients with HF. Depletion of iron stores in the bone marrow is a highly specific for iron deficiency, as it is not affected by inflammation and therefore the test for iron stores in the bone marrow is the gold standard for diagnosis, however its use in clinical practice is limited due to invasiveness and high cost. Diagnostic markers such as levels of hepsidin, dissolved transferrin receptor and ferritin index have low availability in laboratories. Since timely diagnosis followed by treatment of anemia and iron deficiency in patients with CHF impoves the quality of life of patients, therefore, increasing the diagnostic value of tests to identify iron deficiency remains a question for active research.